penalized: A MATLAB Toolbox for Fitting Generalized Linear Models with Penalties - McIlhagga, William (Journal of Statistical Software, 2016)
penalized is a flexible, extensible, and efficient MATLAB toolbox for penalized maximum likelihood. penalized allows you to fit a generalized linear model (gaussian, logistic, poisson, or multinomial) using any of ten provided penalties, or none. The toolbox can be extended by creating new maximum likelihood models or new penalties. The toolbox also includes routines for cross-validation and plotting.